'The Danes don't get this': the economic crash and Icelandic postcolonial engagements. Issue 1 (2nd January 2016) - Loftsdóttir, Kristín
Abstract : In the early 2000s, Iceland enjoyed an extensive boom period that ended abruptly with an economic crash in 2008. This paper focuses on how Iceland's past as a Danish dependency was revisited in the economic boom period. The Danes were widely seen as the former colonial rulers who were 'jealous' of Icelanders' success, in turn, giving the Icelandic national identity a stronger coherence. The concept 'colonialism without colonies' is applied to the Icelandic situation in terms of its potential and limitations, emphasising that a nuanced look at colonialism has to involve the consideration of contradictory desires and subject positions.